An updated estimate of costs of endophthalmitis following cataract surgery among Medicare patients: 2010–2014 - Schmier JK (Dove Medical Press, 2016)
Jordana K Schmier,1 Carolyn K Hulme-Lowe,1 David W Covert,2 Edmund C Lau3 1Exponent, Inc., Health Sciences, Alexandria, VA, 2Alcon Research Ltd., Fort Worth, TX, 3Exponent, Inc., Health Sciences, Menlo Park, CA, USA Background: Endophthalmitis, which can occur after ophthalmic surgery, is an inflammation of the intraocular cavity and causes temporary or permanent vision impairment. However, little is known about the cost of treatment. The objective of this analysis was to update and expand upon the results of a previously published report that estimated the direct medical cost of treatment for endophthalmitis. Methods: Retrospective data analysis using 2010 through 2014 United States Medicare Limited Data Sets. Procedure codes were used to identify beneficiaries who underwent cataract surgery; demographic and clinical characteristics at the time of diagnosis were determined. Patients were stratified into cases (those who developed endophthalmitis) and controls (those who did not develop endophthalmitis) in the 3 months following surgery. Claims (ie, charges) and reimbursements (ie, costs) for cases and controls in the 6 months following cataract surgery were identified and compared. Results are presented in 2015 US dollars. Results: Of a total of 153,860 cataract surgery patients, 181 were diagnosed with endophthalmitis following cataract surgery, at a rate of 1.2 per 1,000. Cases were more likely to be male and less likely to be white than controls; age was similar. Total medical claims and reimbursements as well as ophthalmic claims and reimbursements were significantly higher for cases compared with controls. Total reimbursements, adjusted for age, sex, and region, were $4,893 higher (83% greater) and adjusted ophthalmic reimbursements were $3,002 higher (156% greater) for cases than for controls. Claims and reimbursements were significantly higher across all types of Medicare cost components. Conclusion: Postcataract surgery endophthalmitis is associated with a substantial cost. Successful prophylaxis with antibiotic agents would reduce the significant costs associated with treating endophthalmitis. Keywords: costs and cost analysis, endophthalmitis, eye infections, bacterial, health care costs